Pemanfaatan Deep Learning dalam Kurikulum Pembelajaran Abad 21: Sebuah Tinjauan Literatur - Muhammad Zain; Muhammad Sonhaji Akbar (SISFOTENIKA, 2025)
The transformation of education today is highly dependent on the use of technology, aiming to prepare students who are skilled, adaptive, and ready to compete in the industrial world. This study aims to systematically examine the use, role, and challenges of implementing Deep Learning as part of Artificial Intelligence in the renewed educational curriculum. The study employs a Systematic Literature Review, and its data comes from 28 scientific articles, journals, and research reports that examine the application of Deep Learning technology in education. The research data were analyzed based on themes to identify roles, uses, benefits for 21st-century skills, and difficulties in implementation. The results of the study indicate that Deep Learning plays a significant role in learning that is tailored to student needs through an adaptive system, helps develop appropriate skills in the 21st century (4C), and improves methods for analyzing educational data for early intervention.